Method for layer-by-layer construction of constructed article with viscosity-modified binder
By adding furfurfurol and viscosity modifier to the binder for constructing the three-dimensional structure, combined with acid hardener, the problems of unstable viscosity and insufficient strength of the binder in inkjet printing are solved, and a higher structural strength is achieved and stability.
Patent Information
- Application Number
- CN202380040116.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-13
- Filing Date
- 2023-05-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The adhesive used in the prior art for producing three-dimensional structures layer by layer is unstable during inkjet printing, which easily leads to print head clogging and droplet generation, and lacks strength and disintegration performance after metal casting.
Using a binder containing furfuryl alcohol and a viscosity modifier, ensure the binder by adjusting the viscosity to 5 mPas to 40 mPas at 25°C and adding acid to the construction material mixture as a hardener, combined with novolac as a viscosity modifier. stability and strength.
The stable application of adhesive during inkjet printing is achieved, which significantly improves the strength and storage stability of the constructed structure, and ensures good disintegration performance and pressure stability after metal casting.
Smart Images

Figure BDA0005130899150000091 
Figure BDA0005130899150000121 
Figure BDA0005130899150000131
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a three-dimensional building structure layer by layer. The building structure produced in this way is suitable, among other things, as a core or mold and for metal casting. The building structure produced in this way can also be used for other applications than metal casting. The invention also includes a binder and a kit comprising a binder and a hardener separately therefrom. Background Art
[0002] Prior art
[0003] The term "molded body" refers to the core and the mold (alone or together) used for metal casting. The molded body consists essentially of a core and a mold, which represent the negative mold of the casting to be produced. These cores and molds consist of a refractory material (e.g. quartz sand) and a suitable binder, which give the molded body sufficient mechanical strength. The refractory molding substrate is in a free-flowing form. The binder forms a firm bond between the particles / grains of the molding substrate, so that the molded body has the required mechanical stability.
[0004] Moulded bodies have to meet various requirements. During the casting process itself, they must first of all have sufficient strength and temperature resistance to be able to hold the liquid metal in the cavity formed by one or more casting (part) moulds. Once the solidification process begins, the mechanical stability of the casting is ensured by the layer of solidified metal that forms along the walls of the moulded body. The material of the moulded body must now decompose under the influence of the heat emitted by the metal in such a way that it loses its mechanical strength, i.e. the cohesion between the individual particles / grains of the refractory material is destroyed. Ideally, the moulded body disintegrates back into fine sand, which can be easily removed from the casting.
[0005] In addition to metal casting, products from methods with layer-by-layer construction can also be used for other purposes. Artworks, such as figurines and metal or ceramic products, which are usually transformed into finished components by post-processing steps, can be mentioned here as examples, but are not limited thereto. These products are referred to as built structures hereinafter. The term "built structure" is broader than molded bodies and includes these and therefore also molds and / or cores for metal casting.
[0006] The term "3D printing" refers to various methods for producing three-dimensional objects by building them up layer by layer. One advantage of these methods is the ability to produce complex one-piece bodies with undercuts and cavities. With traditional methods, these bodies must be assembled from several separately produced parts. Another advantage is that these methods can produce bodies directly from CAD data without the need for molding tools.
[0007] If the binder or binder components are to be applied through the nozzles of a print head, the 3D printing method places new demands on the binder which holds the built structure / molded body together. In this case, the binder must not only have a sufficient strength level and good disintegration properties after metal casting, as well as sufficient thermal stability and storage stability, but must also be "printable", i.e. the nozzles of the print head should not be clogged with the binder and the binder should not be able to flow directly out of the print head, but should form individual droplets.
[0008] Various methods are known for the layer-by-layer production of building structures. With the help of these methods, even bodies with the most complex geometries can be produced layer by layer using 3D printing directly from CAD data without the need for molding tools. This is not possible with conventional mold-based methods.
[0009] WO 01 / 68336A2 discloses different binders for layer-by-layer production. In addition, the use of an unspecified furan resin containing at least 50% furfuryl alcohol and about 4% ethylene glycol as a binder component is mentioned. The resin component of the binder is sprayed layer by layer on the entire working surface of the loose molding substrate and then also cured layer by layer, but a hardener, such as an organic acid, is selectively applied. Toluenesulfonic acid is disclosed as an organic acid. In this method, high binder consumption proves to be disadvantageous and expensive because the entire working surface is sprayed with the resin component. WO 01 / 72502A1 changes this method, in which both a liquid binder (also including a furan resin not described in detail) and a liquid hardener (such as toluenesulfonic acid) are applied in sequence in the order of the resin components, and then the hardener is selectively applied layer by layer to the partial area to be hardened.
[0010] Another method for producing cured three-dimensional moldings layer by layer is disclosed in WO 2018 / 224093 A1. In this publication, a resin component is used, which comprises a furan resin as a reaction product of at least an aldehyde compound and furfuryl alcohol and optionally a compound containing nitrogen and / or a phenolic compound, wherein the nitrogen content of the resin component is less than 5 wt.%, and wherein the resin component contains more than 5 wt.% and less than 50 wt.% of monomeric furfuryl alcohol, based on the resin component.
[0011] In WO 2004 / 110719 A2, the order of addition is reversed. First, the molding substrate is premixed with the hardener and then the resin component is selectively applied layer by layer. Acids, amines and esters are mentioned as hardeners. The hardeners are not described in detail. The resin component is described as having a viscosity of 5 to 60 mPas at 20°C.
[0012] DE 102014106178 A1 describes a method for the layer-by-layer production of bodies, in which a molded substrate is cured layer by layer using a resol resin and an ester.
[0013] In particular, acid / furan resin systems according to WO 2004 / 110719 A2 and ester / resole phenolic resin systems according to DE 102014106178 A1 have been widely used in practice for the layer-by-layer production of moulded bodies and for the development of new castings and for the production of individual parts or small series where conventional production using moulding tools is too complicated and expensive or is only suitable for complex core packaging.
[0014] A disadvantage of acid / furan resin systems is that application of the adhesive using an inkjet print head can be severely impaired if the viscosity of the adhesive is too low. This can lead to uncontrolled leakage of adhesive from the print head or to uncontrolled droplet generation by the print head. This applies in particular to adhesives containing a high proportion of monomeric furfuryl alcohol. In addition, the viscosity of the adhesive can vary greatly depending on the changing process temperature, as described, for example, in WO 2004 / 110719 A2. Summary of the invention
[0015] Purpose of the Invention
[0016] The object of the present invention is therefore to provide a method for the layered production of three-dimensional molded bodies or structures, in which the binder used can be optimally applied, for example by an inkjet print head, due to an adapted viscosity. In addition, the molded body or structure should have good strength.
[0017] This problem is solved by a method having the features of the independent claim. Advantageous further developments of the method according to the invention are the subject matter of the dependent claims or are described below.
[0018] The present invention relates to a method for producing a building structure layer by layer from a building material mixture, the building material mixture comprising at least a building base material, a hardener and a binder, the method comprising at least the following steps:
[0019] a) providing at least one building substrate, a hardener and a binder;
[0020] b) spreading at least a layer (thin layer) which structures the substrate with a layer thickness of 0.05 mm to 3 mm, preferably 0.1 mm to 2 mm and particularly preferably 0.1 mm to 1 mm;
[0021] c) printing selected areas of the layer with a binder comprising at least furfuryl alcohol and a viscosity modifier; and
[0022] d) repeating steps b) and c) several times;
[0023] wherein the hardener is spread in the substrate or applied to the layer as part of the layer, or both; and
[0024] wherein the hardener is an acid or contains an acid;
[0025] wherein the viscosity modifier is a novolak dissolved in the binder, and
[0026] The adhesive has a viscosity of 5 to 40 mPas at 25°C.
[0027] The building material mixture includes at least a building base material, a hardener and a binder.
[0028] The hardener can be incorporated into the build substrate or applied to the layers, for example every second layer or every third layer. Typically, the hardener is then applied to each layer. For example, the hardener can be applied using a sprayer or a press head. The proportion of hardener is preferably 0.05 wt.% to less than 3 wt.% hardener based on the build material mixture.
[0029] The binder contains furfuryl alcohol and a viscosity modifier dissolved therein (mandatory component) and possibly other optional components.
[0030] According to one embodiment, the proportion of furfuryl alcohol in the binder is generally greater than 60 wt.%, preferably greater than 75 wt.%, particularly preferably greater than 80 wt.%, and very particularly preferably greater than 90 wt.%. According to one embodiment, apart from the novolac, no further resins are used in the binder.
[0031] The binder has a viscosity of 5 to 40 mPas at 25° C. The viscosity modifier is a novolac. The novolac preferably has a number average molecular weight of greater than 300 g / mol.
[0032] In particular, the binder contains 0.1 wt.% to 25 wt.% or 0.1 wt.% to 12 wt.%, preferably 2.0 wt.% to 9.0 wt.%, and particularly preferably 3.0 wt.% to 8.0 wt.% of novolac.
[0033] It has been found that the viscosity modifier has good solubility in the binder. In particular, the novolac is added in solid form and then dissolved in the binder. To accelerate the dissolution, it is preferably dissolved by heating to above 30°C.
[0034] According to one embodiment, the build material mixture does not contain any formaldehyde donors, such as hexamethylenetetramine, because hardening is performed by acid hardening of the furfuryl alcohol rather than by reaction of the hexamethylenetetramine with the novolac.
[0035] In addition to furfuryl alcohol and viscosity modifier, the binder may also contain optional components. The total amount of the optional components in the binder is preferably less than 39.9 wt.% based on the total amount of the binder, particularly preferably less than 20 wt.% based on the total amount of the binder, and particularly preferably less than 15 wt.% based on the total amount of the binder, or even less than 10 wt.%. The optional components must be dissolved in the binder. In each case, these proportions add up to 100 wt.%.
[0036] The binder is selectively applied by means of a printing device onto the spread film which comprises at least the building substrate and, for example, possible building and molding base additives or possible hardeners.
[0037] The binder is furfuryl alcohol in which the viscosity modifier is dissolved and optionally any optional components are dissolved therein. The hardener is not part of the binder. In addition to the binder, the binder system also includes at least the hardener. The binder is printed as a uniform printing fluid using the nozzle of the print head.
[0038] Furthermore, the invention relates to a building structure, in particular a molded body which can be produced by the method according to the invention. The building structure can be used for a variety of applications and its intended use is not further restricted.
[0039] Furthermore, the invention relates to a moulding which can be produced by the method according to the invention.The moulding is used or intended for use in metal casting, in particular iron, steel, copper or aluminium casting.
[0040] If the build material mixture is used for producing a molding, it can also be referred to as a molding material mixture, and the build substrate is analogous to a molding substrate.
[0041] It has been observed that viscosity modifiers lead to reduced strength of moulded parts produced by hand moulding in a NoBake process (hereinafter referred to as standard NoBake process) compared to a binder having the same structure but lacking the viscosity modifier.
[0042] Surprisingly, it has been found that the binders according to the invention, which are the object of the present invention, apart from the viscosity modifier, have significantly higher strength in 3D procedures than binders of the same structure.
[0043] Furthermore, the binder according to the invention (containing the viscosity modifier) proved to be very stable in storage, had good compatibility and showed good pressure stability compared to a binder of the same composition except for the viscosity modifier.
[0044] Further claimed is a kit comprising a binder and, separately, a hardener comprising an acid. DETAILED DESCRIPTION
[0045] The components of this approach are described in more detail below:
[0046] Build substrate
[0047] The subsoil is an inorganic material in particulate form. The building substrate is not particularly limited. According to another embodiment, the building substrate is silicon carbide or possibly another sinterable material. In this case, a building structure is produced and then sintered.
[0048] According to another preferred embodiment, the building substrate is a refractory molding substrate (in particular when used for producing a molding material mixture).
[0049] The refractory molding substrate is not particularly limited. All particulate solids can be used as refractory molding substrate / building substrate. The refractory molding substrate preferably has a free-flowing state. Common and known materials in pure form and mixtures thereof can be used as refractory molding substrates for producing molded bodies. Suitable materials include, for example, quartz sand, zircon sand or chrome ore sand, olivine, vermiculite, bauxite, refractory clay, and artificially produced refractory molding substrates or those that can be obtained from synthetic materials, such as glass beads, glass particles, hollow aluminum silicate microspheres and mixtures thereof. For cost reasons, quartz sand is particularly preferred. Therefore, the refractory molding substrate is preferably composed of more than 90wt.% of quartz sand.
[0050] Refractory molding substrates are understood to be materials with a high melting point (melting temperature). Preferably, the melting point of the refractory molding substrate is at least about 600°C, preferably at least about 900°C, particularly preferably at least about 1200°C and especially preferably at least about 1500°C.
[0051] The average particle size of the refractory molding substrate is generally about 30 μm to about 500 μm, preferably about 40 μm to about 400 μm and particularly preferably about 50 μm to about 250 μm. The particle size can be determined by sieving in accordance with DIN ISO 3310, for example.
[0052] The proportion of the building substrate or refractory molding substrate in the building material mixture is not particularly limited. The building substrate or refractory molding substrate preferably accounts for at least about 80wt.%, particularly at least about 90wt.%, and particularly preferably at least about 93wt.% of the building material mixture or molding material mixture.
[0053] Building substrate and molding substrate additives
[0054] In addition to the building substrate / refractory molding substrate, the building material mixture may also contain other solids. In the context of the present invention, these are referred to as building or molding base additives. They are usually particulate solids. The average particle size of the building and molding base additives is usually from about 30 μm to about 500 μm, preferably from about 40 μm to about 400 μm, and particularly preferably from about 50 μm to about 250 μm. The particle size can be determined, for example, by sieving according to DIN ISO 3310.
[0055] The building base or refractory molding base, hardener and binder and optional building or molding base additives (if present) are called the building material mixture. Examples of building or molding base additives are organic or mineral additives such as iron oxides, silicates, aluminates, wood flour or starch and mixtures thereof. These can be added to the refractory molding base to prevent casting defects.
[0056] The amount of the building or molding base additive is not particularly limited and is generally up to about 10 wt.%, preferably up to about 7 wt.%, and particularly preferably up to about 1 wt.%, based on the building or molding base mixture.
[0057] In a preferred embodiment, amorphous SiO2 is used as a build or mold substrate additive.
[0058] The build and molding base additives are applied to the thin layer in a distributed manner. There is no selective application of the build or molding base additives.
[0059] Hardener
[0060] The hardener is an acid or contains an acid. Among the hardeners used for curing the binder, conventional acids used for foundry mold production or their mixtures (whose pK at 25°C is s The value is less than 4, preferably pK s Value is less than or equal to 3.9, preferably pK s The value is less than 3 and the pK is particularly preferred s Values of less than 1.5 (in each case at 25° C.)), such as organic acids, such as p-toluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, methanesulfonic acid or lactic acid, and inorganic acids, such as sulfuric acid or phosphoric acid or mixtures of various organic and inorganic acids. The hardener may also contain water. Particularly preferred hardeners are aqueous p-toluenesulfonic acid, sulfuric acid and / or lactic acid and mixtures thereof.
[0061] The amount of hardener (including any optional aqueous dilution) in the building material mixture / molding material mixture is in particular 0.05 wt.% to 3 wt.%, preferably 0.1 wt.% to 2.5 wt.% and particularly preferably 0.1 wt.% to 2 wt.%, based in each case on the building or molding material mixture.
[0062] Furthermore, the hardener may contain additives, in particular to optimize the properties of the sand. These include, for example, hardening regulators, such as glycols, in particular ethylene glycol, or alcohols, such as ethanol, in an amount of 0 wt.% to 15 wt.%, preferably 0 wt.% to 10 wt.%, and in particular 0 wt.% to 7 wt.%, based on the hardener.
[0063] The hardener can also be selectively applied to the thin layer of the build material mixture in an additional process step. The selective application of the hardener can be carried out using an additional integrated application mechanism, such as an inkjet print head or a spray device.
[0064] In a preferred embodiment, the hardener is added / mixed into the build material mixture prior to thin layer spreading and is not applied selectively.
[0065] Binder
[0066] The binder contains furfuryl alcohol. The proportion of furfuryl alcohol in the binder is generally greater than 60 wt.%, preferably greater than 75 wt.%, particularly preferably greater than 80 wt.%, and very particularly preferably greater than or equal to 88 wt.% or greater than 90 wt.%. According to one embodiment, no other resin is used in the binder except the novolac.
[0067] The binder has a viscosity of 5 to 40 mPas, preferably 6 to 30 mPas, particularly preferably 7 to 20 mPas, and most preferably 8 to 13 mPas at 25° C. The viscosity is measured on a Brookfield rotational viscometer using a measuring geometry axis 18 at a viscosity of up to 16 mPas and a speed of 200 rpm, and using a measuring geometry axis UL adapter at a speed of 50 rpm at a viscosity of less than 16 mPas. Unless otherwise stated, the viscosity is measured at 25° C. in each case.
[0068] The binder preferably has a surface tension of 15 to 65 mN / m, preferably 20 to 50 mN / m, particularly preferably 25 to 45 mN / m and very particularly preferably 30 to 40 mN / m. The surface tension is measured using the ring method according to De Noüy (at 25° C.).
[0069] The binder preferably has a viscosity of 1.0 g / cm 3 Up to 1.5g / cm 3 , particularly preferably 1.05 g / cm 3 Up to 1.4g / cm 3 , particularly preferably 1.05 g / cm 3 Up to 1.2g / cm3 , and most preferably 1.1 g / cm 3 Up to 1.2g / cm 3 Density. Density was measured at 20°C using the oscillating U-tube method.
[0070] The binder preferably has a pH value of 3 to 9, preferably a pH value of 4 to 8, particularly preferably a pH value of 5 to 7.5 and very particularly a pH value of 6 to 7.5.
[0071] The amount of binder is preferably 0.1 to 10 wt. %, preferably 0.5 to 7.5 wt. % and in particular 0.8 to 4 wt. %, based in each case on the building or molding material mixture.
[0072] Viscosity Modifiers
[0073] The binder contains novolac to adjust the viscosity. Novolacs are storage-stable methylene-bridged phenolic resins in which the ratio of aldehyde to phenol or the ratio of formaldehyde to phenol is less than 1:1, which are prepared by polycondensation of the reactants in the presence of catalytic amounts of acids or metal salts. Preferably, an acidic condensation is carried out, i.e. preferably an acid is used.
[0074] Typically, the ratio of aldehyde to phenol in the novolac is from 0.3:1 to less than 1:1, preferably from 0.4 to 0.9:1, particularly preferably from 0.6:1 to 0.9:1.
[0075] Phenols, such as phenol and / or substituted phenols, are suitable monomers for producing novolacs. In addition to phenol, cresol or nonylphenol, examples are 1,2-dihydroxybenzene (catechol), 1,3-dihydroxybenzene (resorcinol), or 1,4-dihydroxybenzene (hydroquinone) and / or substituted phenols, such as cashew nut shell liquid, i.e. a mixture of cardanol and cardanol diphenol, bisphenol A, bisphenol F, bisphenol S or mixtures thereof. Phenol is particularly preferred, for example, based on the molar amount of phenol incorporated in the novolac, for example more than 90 mol % of phenol or even more than 95 mol % of phenol.
[0076] Suitable aldehydes are, for example, formaldehyde, for example in the form of an aqueous solution or as a polymer in the form of paraformaldehyde, butyraldehyde, glyoxal and mixtures thereof. Particularly preferred is formaldehyde or a mixture containing predominantly formaldehyde (based on the molar amount of aldehydes, for example greater than 90 mol % formaldehyde or even greater than 95 mol % formaldehyde).
[0077] Acids such as hydrochloric acid, sulfuric acid, phosphoric acid, sulfonic acid, oxalic acid or salicylic acid or anhydrides such as maleic anhydride are used as catalysts for the preparation of novolacs. Oxalic acid is preferably used. Another possibility is to add metal salts, for example Zn(II), Mg(II) or Cu(II) salts, for example acetates, in catalytic amounts.
[0078] A typical feature of novolacs is the following structural unit with methylene bridges, where the predominant ortho-ortho bond is only one of the possible bonds, although the preferred one. Some, but preferably very few, of the phenol groups (eg less than 10 mol %) may also be substituted or have other hydroxyl groups.
[0079]
[0080] The novolacs used can take essentially any form, such as powders, flakes or pastilles. They are preferably used in powder form (at 25° C.) and then dissolved in a binder or furfuryl alcohol.
[0081] The free phenol content of the novolac used is in particular less than 5.0 wt.%, more preferably less than 1.0 wt.%, even more preferably less than 0.5 wt.% and most preferably less than 0.2 wt.%. The free phenol content is measured by gas chromatography (GC) in accordance with DIN 16916-02-L2 / DIN EN ISO 8974.
[0082] The amount of the viscosity modifier is 0.1 wt.% to 12.0 wt.%, preferably 2.0 wt.% to 9.0 wt.%, and most preferably 3.0 wt.% to 8.0 wt.%, based on the binder as a whole.
[0083] The number average molecular weight of the viscosity modifier is in particular greater than 300 g / mol, preferably greater than 500 g / mol and particularly preferably greater than 600 g / mol. The number average molecular weight of the viscosity modifier is in particular greater than 500 g / mol, preferably greater than 1500 g / mol, particularly preferably greater than 2500 g / mol and very particularly preferably greater than 3500 g / mol. The molar mass (number average) of the viscosity modifier is preferably less than 50,000 g / mol, preferably less than 25,000 g / mol. The molecular weight is measured by gel permeation chromatography (GPC) in THF according to DIN 55672-1.
[0084] The novolac used may contain hexamethylenetetramine. It is particularly preferred to use the novolac in the absence of hexamethylenetetramine, ie the hexamethylenetetramine is not added to the building substrate nor to the binder.
[0085] The production of novolacs has been known to the person skilled in the art for a long time and is described in detail, for example, by L. Pilato in his book “Phenolic Resins: A century of Progress” (published by Springer Verlag in 2010), in Chapters 4 and 7, in particular 4.3.1 to 4.3.4.
[0086] Optional components of the binder
[0087] The binder may contain other optional components, such as other resins (other than novolac), water, glycols, alcohols, phenolic compounds, solvents, silanes, plasticizers, cure modifiers, surface modifiers or surface-active substances.
[0088] The binder may also contain phenol, phenol compounds, resins, water, glycols, alcohols, solvents and / or silanes, especially individually and / or in a total amount of 0.01 wt.% to 15 wt.%, preferably 2 wt.% to less than 12 wt.%, and particularly preferably 5 wt.% to less than 10 wt.%, based on the binder.
[0089] Optionally, phenolic compounds can be included in the binder to improve the technical properties of the sand, such as its strength. Phenolic compounds are phenol and substituted phenols. Phenols are characterized by one or more aromatic rings and at least one hydroxyl substitution on these aromatic rings. In addition to phenol itself, examples also include phenols such as cresol or nonylphenol, 1,2-dihydroxybenzene (catechol) or 1,3-dihydroxybenzene (resorcinol), such as cashew nut shell oil, i.e. a mixture of cardanol and cardanol diphenol, 1,4-dihydroxybenzene (hydroquinone), bisphenol A, bisphenol S or bisphenol F or mixtures thereof. Particularly preferred is resorcinol as the phenolic compound. Substituted phenols are phenols substituted by hydrocarbon groups and / or bridged by hydrocarbons. Therefore, phenolic compounds as optional components are compounds that fall into the group of phenol or substituted phenols. Novolac or another polymer containing phenol as a monomer component is not a phenolic compound in the sense of the present invention.
[0090] As optional components, the binder preferably contains silanes which contain silicon-O-(C1-C4-alkyl) groups and possibly also silicon-(C1-C4-alkyl) and / or -(C1-C4-alkylene)-amino) groups. A preferred representative of these is aminopropyltriethoxysilane.
[0091] The binder may also optionally contain other resins (different from novolac) dissolved in the furfuryl alcohol of the binder. If another resin is added to the binder, the resin preferably comprises a furan resin. The furan resin is not particularly limited and may be any furan resin known in the art.
[0092] For example, the furan resin may be a polymer of furfuryl alcohol and / or furan, or may be a polymer containing formaldehyde, urea and / or phenol as one or more other monomers in addition to furfuryl alcohol and / or furan.
[0093] The proportion of optional other resins, in particular furan resins, in the total binder is less than 15 wt.%, preferably less than 12 wt.%, and particularly preferably less than 10 wt.%, in particular greater than 2 wt.%, and in particular greater than 5 wt.%.
[0094] The proportion of the optional components in the binder is generally less than 39.9 wt.%, or preferably less than 20 wt.%, or less than 15 wt.%, and particularly preferably less than 10 wt.%.
[0095] If the resin is not used as an optional component, the proportion of the resin used as an optional component is preferably less than 20 wt.%, or less than 15 wt.%, and particularly preferably less than 10 wt.%.
[0096] method
[0097] Once strength permits, the unbound build material mixture (where no binder is applied, or even no hardener if a hardener is also selectively applied) can be removed from the build structure and the build structure can be further processed, such as in preparation for metal casting. For example, the unbound build material mixture can be removed from the bound build material mixture by a spout so that the unbound build material mixture can trickle out.
[0098] For example, the bound build material mixture (build structure) can be freed of residues of unbound build material mixture using compressed air or by brushing.
[0099] The unbound build material mixture can be reused in a new printing process.
[0100] For example, printing is performed using a print head with a large number of nozzles, wherein the nozzles are preferably individually selectively controllable. According to another embodiment, the print head is moved by a computer in at least one plane, and the nozzles apply the liquid binder layer by layer. For example, the print head can be a drop-on-demand inkjet print head with bubble jet or preferably piezo technology.
[0101] Example
[0102] The present invention is explained below with reference to experimental examples, but is not limited thereto.
[0103] Unless otherwise indicated, all ratios and percentages are by weight.
[0104] Example 1: Strength of a building structure produced in a standard no-bake process
[0105] In order to compare the strength development of different binders, quartz sand H32 from Quarzwerke Group Haltern was placed in a blade mixer from Beba. 1.0 wt.% of binder, based on the sand, and then 0.4 wt.% of sulfonic acid hardener, based on the sand, were added and mixed thoroughly with the build base for 1 minute (Mixture 1).
[0106] As comparative binder 1 (V), a commercial product having a viscosity of 9 mPas at 25° C. (more than 87 wt. % furfuryl alcohol and bisphenol-A, and less than 0.5 wt. % silane) was used.
[0107] Binder 2 (greater than 87 wt.% furfuryl alcohol) was prepared by adding 6.5 wt.% of novolac as viscosity modifier, also adjusted to 9 mPas at 25° C. Both binders contained the same type and amount of silane as an optional component.
[0108] The novolac had a number average molecular weight of 697 g / mol. The SDV precolumn equipped with an 8x50 mm column, a linear SDV column (5 μm, ) and linear SDV columns (5 μm, The molecular weight was determined by GPC chromatograms generated on an Agilent 1100 series instrument with a flow rate of 1 mL min at 35 °C. -1 Each sample was measured at a flow rate of 100 nm (in THF) and polystyrene 700000 as internal standard and calibrated with polystyrene standards. Detection was performed using the UV signal (271 nm). Alternatively, detection can also be performed by the refractive index (RI). Detection is preferably performed by the UV signal (271 nm). The chromatogram was analyzed using WinGPC software. SDV stands for divinylbenzene cross-linked polystyrene.
[0109] The following samples were used:
[0110] Binder 1 (V): Furfuryl alcohol plus bisphenol-A and silane (viscosity at 25°C: 9 mPas)
[0111] Binder 2: Furfuryl alcohol plus novolac as viscosity modifier and silane: 6.5% novolac (viscosity at 25°C: 9 mPas)
[0112] For the strength test, rectangular test bars (Georg Fischer bars) with the dimensions of 171 mm x 22.36 mm x 22.36 mm were produced. For this purpose, a portion of the produced molding material mixture was filled into a molding box with 12 engravings of the above-mentioned dimensions and compacted by vibration for 30 seconds. After 30 minutes, the test bars were removed from the engravings in the molding box.
[0113] The strength was tested by measuring the three-point bending strength on a Jung SJ1 strength testing machine from Jung Instruments.
[0114] The flexural strength is determined after:
[0115] - 1 hour after molding
[0116] -2 hours after molding
[0117] - 4 hours after molding
[0118] -24 hours after molding
[0119] The obtained intensities are summarized in Table 1 .
[0120] Table 1. Strength of different adhesives after 1 hour, 2 hours, 4 hours and 24 hours (V: comparative).
[0121]
[0122] In the standard no-bake process, a decrease in strength is observed due to the addition of novolac.
[0123] Example 2: Strength of built structures produced in 3D printing
[0124] In order to compare the strength development of different binders in the 3D printing process, a precursor of quartz sand GS14 (average grain size 0.14 mm, a product of Strobel) was first proposed and mixed with 0.20 wt.% of a sulfonic acid-based hardener based on sand in a blade mixer to prepare molding material mixture 2. The hardener was a 65 wt.% aqueous solution of p-toluenesulfonic acid.
[0125] The build structure was produced on a commercial printing system (VX 200 from Voxeljet AG, with a piezoelectric inkjet print head). In the printer's build chamber, a preliminary stage of a build material mixture of 0.28 mm thickness was spread layer by layer using a vibration-supported application process and smoothed using a metal blade. In the next step, a binder was selectively applied according to the provided CAD data. Bent bars with dimensions of 22.36 mm x 22.36 mm x 170.00 mm were produced as build structures. Based on the volume of the build material mixture, the amount of binder added was always set to 1.85 vol.%. After 12 hours, strength and loss on ignition were tested at 900 ° C and a holding time of 3 hours.
[0126] As comparative binder 1 (V), a binder having a viscosity of 9 mPas at 25° C. (greater than 87 wt. % furfuryl alcohol plus bisphenol-A, and less than 0.5 wt. % silane) was used.
[0127] Printing performance depends on viscosity. Therefore, binder 2 (greater than 87 wt. % furfuryl alcohol) was also adjusted to 9 mPas by adding 6.5 wt. % of novolac as viscosity modifier. Both binders contained the same type and amount of silane as optional component.
[0128] The following samples were produced:
[0129] Binder 1 (V): Furfuryl alcohol plus bisphenol-A and silane (viscosity at 25°C: 9 mPas)
[0130] Binder 2: Furfuryl alcohol plus novolac as viscosity modifier and silane: 6.5% novolac (viscosity at 25°C: 9 mPas)
[0131] The strength was tested by measuring the three-point bending strength on a Jung SJ1 strength tester from Jung Instruments. The strengths and ignition losses obtained are shown in Table 2 given below.
[0132] Table 2: Strength and LOI of different binders with adjusted viscosity, and the corresponding LOI at 900°C and 3 hours holding time (V: Comparative)
[0133]
[0134] The LOI shows that both build structures contain the same amount of binder. Therefore, the build material mixes tested are comparable.
[0135] Surprisingly, it was found that the strength of Binder 2 in 3D printing was significantly higher than Binder 1 (V). Surprisingly, it was found that the binder according to the invention, except for the viscosity modifier, produced significantly higher strength in the 3D process compared to a binder with the same structure, which could not be derived from the strength in the standard no-bake procedure (Comparative Example 1), since the addition of novolac to the binder was associated with a loss of strength therein.
Claims
1. A method for producing a building structure layer by layer from a building material mixture, the building material mixture comprising at least a building base material, a hardener and a binder, the method comprising at least the following steps: a) providing at least a building base material, a hardener and a binder; b) spreading at least a layer of said building substrate with a layer thickness of 0.05 mm to 3 mm; c) printing selected areas of the layer with a binder comprising at least furfuryl alcohol and a viscosity modifier; as well as d) repeating steps b) and c) several times; wherein the hardener is spread in the build substrate as part of the layer, or the hardener is applied to the layer, or both; wherein the hardener is an acid or contains an acid; wherein the viscosity modifier is a novolac dissolved in the binder; and The binder has a viscosity of 5 to 40 mPas at 25°C.
2. The method according to claim 1, wherein the binder comprises more than 60 wt.%, preferably more than 75 wt.%, more preferably more than 80 wt.%, and particularly preferably more than 90 wt.% of furfuryl alcohol.
3. The method according to at least one of the preceding claims, wherein the binder comprises 0.1 to 25 wt.%, 0.1 to 12 wt.%, preferably 2.0 to 9.0 wt.%, and more preferably 3.0 to 8.0 wt.% of novolac.
4. The process according to claim 1, wherein the novolac is added in solid form to furfuryl alcohol or to the binder and then dissolved in the binder. 5 . The method according to claim 1 , wherein the viscosity modifier has a number-average molecular weight of greater than 300 g / mol, preferably greater than 500 g / mol and particularly preferably greater than 600 g / mol.
6. The process according to claim 1, wherein the novolac has a free phenol content of less than 5.0 wt.%, preferably less than 1.0 wt.%, even more preferably less than 0.5 wt.% and very particularly preferably less than 0.2 wt.%. 7 . The method according to claim 1 , wherein the binder has a viscosity at 25° C. of in each case from 6 to 30 mPas, particularly preferably from 7 to 20 mPas and very particularly preferably from 8 to 13 mPas.
8. The method according to claim 1, wherein 0.05 wt.% to less than 3 wt.%, preferably 0.1 wt.% to 2.5 wt.%, and particularly preferably 0.1 wt.% to 2 wt.%, of hardener, based in each case on the building material mixture, is used.
9. The method according to at least one of the preceding claims, wherein the hardener further comprises glycols, in particular ethylene glycol, and / or alcohols, in particular ethanol, preferably in an amount of more than 0 wt.% to 15 wt.%, based on the hardener.
10. The method according to at least one of the preceding claims, wherein the binder further comprises phenol, phenolic compounds, other resins, water, glycols, alcohols, solvents and / or silanes, in particular in a total amount of 0.01 to 15 wt.%, preferably 2 to less than 12 wt.%, and particularly preferably 5 to less than 10 wt.%, based on the binder.
11. The method according to at least one of the preceding claims, wherein the binder comprises less than 15 wt.%, preferably less than 12 wt.% and particularly preferably less than 10 wt.% of furan resin. 12 . The method according to claim 1 , wherein the building material mixture comprises silicon carbide or another sinterable material as building base material and the building structure is sintered.
13. The method according to at least one of the preceding claims, wherein the building material mixture comprises a building substrate, preferably a refractory molding substrate, and the refractory molding substrate preferably comprises quartz sand, zircon sand, chrome ore sand, olivine, vermiculite, bauxite, refractory clay, glass beads, glass particles, hollow aluminum silicate microspheres and mixtures thereof. 14 . The method according to claim 1 , wherein the building substrate has an average particle size of 30 μm to 500 μm, preferably 40 μm to about 400 μm and particularly preferably 50 μm to about 250 μm.
15. The method according to at least one of the preceding claims, wherein more than 80 wt.%, preferably more than 90 wt.%, and particularly preferably more than 93 wt.% of the building material mixture is a refractory molding substrate. 16 . The method according to claim 1 , wherein the building material mixture also contains amorphous silicon dioxide, in particular in an amount of 1 to 10 wt. %.
17. The method according to at least one of the preceding claims, further comprising the steps of: i) after the layer-by-layer construction is complete, optionally hardening the building structure in an oven or by microwaves to obtain an at least partially hardened building structure, and then ii) removing unbound build material mixture from the at least partially hardened build structure.
18. The method according to claim 1, wherein printing is performed using a print head having a plurality of nozzles, wherein the nozzles are preferably individually selectively controllable, wherein the print head is in particular a drop-on-demand print head having bubble jet or piezo technology.
19. The method of claim 18, wherein the print head is movable in at least one plane under computer control, and the nozzles apply the adhesive at least layer by layer.
20. A mold or core producible by a method according to at least one of the preceding claims for use in metal casting, in particular iron, steel, copper or aluminium casting.
21. A binder having a viscosity of 5 to 40 mPas at 25°C, the binder comprising more than 60 wt.% of furfuryl alcohol and 0.1 wt.% to 12.0 wt.% of at least one novolac.
22. The binder according to claim 21, wherein the binder contains less than 15 wt.%, preferably less than 12 wt.%, and particularly preferably less than 10 wt.% of furan resin.
23. Adhesive according to claim 21 or 22, further characterized by one or more of the features of claims 2 to 7 and 10.
24. Kit comprising a binder according to at least one of claims 21 to 23 and, independently therefrom, a hardener comprising an acid, wherein the hardener is preferably further characterized by claims 8 and / or 9.
